Antidiabetic activity of Physalis angulata L. fruit juice on streptozotocin-induced diabetic rats - Iwansyah, Ade Chandra; Luthfiyanti, Rohmah; Ardiansyah, Raden Cecep Erwan; Nurhaidar, Rahman; Andriana, Yusuf; Hazrulrizawati, Abd Hamid (Elsevier, 2022)
Physalis angulata L. is a plant applied in traditional treatment as a remedy for numerous ailments, which include diabetes mellitus. This study examines the antidiabetic effects of P. angulata fruit extract on streptozotocin-induced type-2 diabetes mellitus in rats. Rats were sorted randomly into five clusters, which are a normal cluster, a diabetic cluster, two diabetic clusters administered with the fruit extract of P. angulata, and a diabetic cluster administered with metformin. The diabetic rats were treated orally using 1 mL and 2 mL of P. angulata fruit extract every day for two weeks. The effects of P. angulata fruit juice were studied by measuring the body weight, Fasting Blood Glucose level, GLUT-4 genes expression and histopathological changes. P. angulata fruit juice significantly decreased the blood glucose level, therefore there is no significant changes of the body weight and upregulate GLUT4 gene expression in the soleus muscle. Histopathological analysis showed significant improvement results of pancreatic tissues that were treated with 2 mL/day compared to 1 mL/day. Furthermore, P. angulata fruit juice contains high concentration of vitamin C and phenolic compounds that could effectively attenuate diabetes. The results obtained provides important information that supports the use of P. angulata fruit in management of diabetes